Interrelation of Self-Report, Behavioural and Electrophysiological Measures Assessing Pain-Related Information Processing - Oliver Dittmar; Rüdiger Krehl; Stefan Lautenbacher (Pain Research and Management)
INTRODUCTION: A number of variables reflecting attentional and emotional mechanisms of processing pain-related information have recently attracted interest, ie, fear of pain, pain catastrophizing, hypervigilance and attentional bias to pain. These variables can be assessed by explicit measures based on conscious self-report, or by implicit measures assessing mainly preconscious stages of information processing such as behavioural or electrophysiological tests. Convergent validity within implicit measures was assumed to be high, as was the discriminant validity between implicit and explicit measures.